Adverse outcomes after major surgery in patients with systemic lupus erythematosus: a nationwide population-based study. Issue 9 (5th June 2013) - Lin, Jui-An; Liao, Chien-Chang; Lee, Yi-Jui; Wu, Chih-Hsiung; Huang, Wen-Qi; Chen, Ta-Liang
Abstract : Objectives: To investigate the postoperative adverse outcomes among surgical patients with preoperative systemic lupus erythematosus (SLE) in a nationwide population-based study. Methods: We used Taiwan's National Health Insurance Research Database to identify 4321 surgical inpatients with SLE and 17 284 sex- and age-matched controls receiving major surgery. Sociodemographic characteristics, preoperative comorbidities, postoperative 30-day in-hospital major complications and mortality were analysed among surgical patients with and without SLE. Results: Surgical patients with SLE had a higher prevalence of preoperative coexisting medical conditions and postoperative major complications. The OR of 30-day postoperative mortality for surgical patients with SLE was 1.71 (95% CI 1.09 to 2.67) after adjustment. Surgical patients who had received more recent (within 6 months) preoperative SLE-related inpatient care had higher risks of 30-day postoperative acute renal failure (OR=7.23, 95% CI 4.52 to 11.6), pneumonia (OR=2.60, 95% CI 1.82 to 3.72), pulmonary embolism (OR=4.86, 95% CI 1.20 to 19.7), septicaemia (OR=3.43, 95% CI 2.48 to 4.74), stroke (OR=2.01, 95% CI 1.38 to 2.92), overall complications (OR=2.30, 95% CI 1.89 to 2.80) and 30-day postoperative mortality (OR=2.39, 95% CI 1.28 to 4.45) than surgical patients without SLE. SLE-related preoperative steroid injections showed a dose-dependent relationship with postoperative complications and mortality. Conclusions: SLE significantly increased the risks of surgical patients for overall major complications and mortality after major surgery. Our findings demonstrated the need for integrated care and revised protocols for perioperative management to improve outcomes for surgical patients with SLE.